Thermodynamic and structural evolution of Dy2Ti2O7 pyrochlore after swift heavy ion irradiation. (15th February 2018) - Chung, Cheng-Kai; Shamblin, Jacob; O'Quinn, Eric C.; Shelyug, Anna; Gussev, Igor; Lang, Maik; Navrotsky, Alexandra
Abstract: Utilizing a combined approach of high temperature calorimetry and neutron total scattering, we obtained critical insights into the energetics and annealing of radiation damage in swift heavy ion irradiated Dy2 Ti2 O7 pyrochlore. Oxide melt solution calorimetry reveals that the radiation amorphized Dy2 Ti2 O7 is destabilized by 243 kJ/mol compared to fully ordered, crystalline pyrochlore. Differential scanning calorimetry of the amorphized sample shows a rapid exothermic event starting at 1063 K, which, based on neutron structural analysis, is related to recrystallization. The heat release on annealing to 1473 K, – 137 kJ/mol, is only about half of the total energetic difference between the ordered crystalline and amorphized samples, despite the apparent recovery of long-range pyrochlore-like ordering. Detailed neutron structural analysis confirms the persistence of residual damage in the 1473 K annealed sample. This metastability is attributed to local disorder in the form of weberite-like short-range domains in the recrystallized material. The annealing of radiation damage appears to be a complex, multistep process with decoupled short- and long-range damage recovery. Heating well above the initial recrystallization temperature does not erase all the damage, which may have important implications for the use of pyrochlores as nuclear waste forms. Graphical abstract: Image 1